Evaluation and optimisation of the performance of a multi-integrated lab-scale plant for the treatment of dairy wastewater - Ramsuroop, Jyestha (Department of Chemical Engineering, 2025)
South Africa's dairy sector, producing 3.4 million tonnes of milk in 2019, generates significant wastewater, estimated at 2.5 times the volume of processed milk, or approximately 8.5 million tonnes annually. This wastewater poses serious environmental risks due to its high organic content, potentially leading to eutrophication and hypoxic zones in water bodies. Effective treatment methods are essential to mitigate these impacts. This study evaluates the performance of a lab-scale wastewater treatment plant, combining various biological processes previously used for abattoir wastewater (AWW), given the similarities between AWW and dairy wastewater (DWW) in terms of high organic and fat content. In anticipation of the challenge of clogging which has been prevalent in previous studies, an investigation was done into the use of okra as a biological coagulant which could possibly be integrated with the system. The research focuses on optimizing individual treatment units and assessing their collective performance in treating DWW. Initial challenges included operational errors, such as the overuse of Morma in pre-treatment, leading to increased biomass production and elevated Chemical Oxygen Demand (COD). Despite subsequent corrections improving system stability, fluctuations persisted, particularly in the Expanded Granular Sludge Bed Reactor (EGSBR). COD removal rates ranged from 60% in week 3 to 26% in week 5, highlighting the system's potential but falling short of traditional anaerobic digestion (AD) systems, which can achieve up to 90% COD removal. However, the system performed better with higher raw COD levels, indicating its efficacy in treating wastewater with elevated COD content. EGSBR stability issues were attributed to clogging and biomass washout, exacerbated by a reduced pre-treatment hydraulic retention time (HRT) of 12 hours. Analysis of fat, oil, and grease (FOG) removal revealed inconsistent performance, with the highest removal rates occurring in weeks with FOG content exceeding 6000 mg/L DWW. FOG removal rates ranged from 27% to 94%, surpassing those of previous AD reactor studies. The observed correlation between FOG content and system performance warrants further investigation. Total Suspended Solids (TSS) removal rates served as indicators of reactor stability issues, with increased TSS indicating biomass washout. Decreasing pre-treatment HRT adversely affected reactor stability, highlighting the importance of optimizing pre-treatment parameters. Additionally, the use of okra seeds as a coagulant was explored, showing promising results in reducing TSS and COD from DWW. The optimal dose was 5g per 2L of DWW, achieving the highest removal rates for both TSS and COD. This suggests that okra seeds offer an eco-friendly alternative to traditional coagulants like alum. Integrating coagulant treatments with biological agents could enhance the removal of solids and FOGs, addressing the stability issues observed in the EGSBR and improving overall system performance.